A case of Kii amyotrophic lateral sclerosis/parkinsonism dementia complex presenting as progressive parkinsonism with corresponding tau imaging. Issue 1 (3rd November 2020) - Ohta, Yasuyuki; Shimada, Hitoshi; Ikegami, Ken; Tsunoda, Keiichiro; Hishikawa, Nozomi; Yamashita, Toru; Takemoto, Mami; Omote, Yoshio; Tagai, Kenji; Matsuoka, Kiwamu; Higuchi, Makoto; Abe, Koji
Abstract: Amyotrophic lateral sclerosis/parkinsonism dementia complex (ALS/PDC), frequently observed in the Kii peninsula of Japan, is pathologically characterized by widespread tau pathology in the cerebrum and brainstem. Here, we report a case of Kii ALS/PDC predominantly presenting progressive parkinsonism. Tau positron emission tomography (PET) imaging with 18 F‐PM‐PBB3 suggested tau deposition in the substantia nigra of the midbrain and subcortical areas, but not in the cerebral cortex, which was similar to progressive supranuclear palsy (PSP), suggesting that parkinsonism‐predominant type of Kii ALS/PDC may have a similar area of tau deposition to PSP.